Folate deficiency inhibits the PCP pathway and alters genomic methylation levels during embryonic development. Issue 9 (25th March 2018) - Geng, Yanqing; Gao, Rufei; Liu, Xueqing; Chen, Xuemei; Liu, Shangjing; Ding, Yubin; Mu, Xinyi; Wang, Yingxiong; He, Junlin
Abstract : Folate deficiency results in abnormal embryonic development, but the underlying mechanisms remain to be comprehensively investigated. Mutation of Vangl genes belonging to the planar cell polarity (PCP) pathway is associated with abnormal embryonic development, but the effect of folate deficiency on the PCP pathway is unclear. In this study, we found that folate deficiency inhibited Vangl gene expression and Vangl protein binding to the ligand Dvl. As a methyl donor, folate can chemically alter the DNA methylation levels of genomic sequences. Here, reduced representation bisulfite sequencing (RRBS) was employed to detect the methylation profiles of mouse embryos. The results confirmed that folate deficiency affected the genomic methylation levels of mouse embryos, which resulted in down‐regulation of key genes involved in embryonic development. Gene ontology (GO) analysis suggested that the genes located in the differentially methylated regions (DMRs) are primarily involved in biological regulation, cellular processes, development, metabolism, and signaling pathways. The data revealed that folate deficiency inhibits the PCP pathway and alters genomic methylation profiles, which may be the underlying mechanisms through which folate deficiency impairs embryonic development. Abstract : (1) This study revealed that folate deficiency inhibits the PCP pathway; (2) Our data revealed that folate deficiency alters genomic methylation profiles of embryos in mice; (3) changes in the PCP pathway and genomic methylation levels may be the underlying mechanisms through which folate deficiency impairs embryonic development.